Factors affecting the accuracy of genomic predictions in testcrosses of maize biparental population - Galić, Vlatko; Mazur, Maja; Brkić, Andrija; Volenik, Mirna; Jambrović, Antun; Zdunić, Zvonimir, agronom; Šimić, Domagoj (2020)
Genomic prediction accuracy (r_MP) is affected by many factors, such as the trait heritability, training population size and structure, and the number of markers. This study’s objective was to investigate the factors associated with r_MP for the ear height and the plant height in two planting densities in testcrosses of maize (Zea mays L.) IBM population. Genetic correlations between the training and validation populations were calculated. The high heritability estimates and correlations between the traits were observed. The non-zero estimates of r_MP for all trait-density combinations implied an efficiency of genomic selection. The lower than expected values of genetic correlations were observed between the training and validation populations. However, a strong correlation was observed between a genetic correlation of training and the validation population and r_MP in all three sizes of training populations assessed (20-40%, 40-60%, and 60-80%), suggesting that the size of the training population can be kept low by an appropriate selection while maintaining a high r_MP. Further studies of relationships between the training and validation populations with larger effective population sizes are suggested, as reducing the size of training population while maintaining a high r_MP can facilitate a more effective allocation of resources in a maize breeding program.
Mnogi faktori, kao što su heritabilnost svojstva, veličina i struktura radne populacije i broj markera, utječu na efikasnost genomskih predviđanja (rMP). Cilj ovoga rada bio je ispitati faktore povezane s rMP za visinu klipa i visinu biljke u dvije gustoće sjetve kod test-križanaca IBM populacije kukuruza (Zea mays L.). Izračunane su genetske korelacije između radne i validacijske populacije. Dobivene su visoke procjene heritabilnosti i korelacije između svojstava. Procjene rMP bile su različite od nule za sve kombinacije svojstvo -gustoća. što ukazuje na efikasnost genomske selekcije. Vrijednosti genetskih korelacija između radne i validacijske populacije bile su niže od očekivanih. Međutim, jaka korelacija dobivena je između genetske korelacije radne i validacijske populacije i rMP za sve tri veličine radne populacije (20-40%, 40-60% i 60-80%). što ukazuje da se uz odgovarajuću selekciju veličina radne populacije može održati niskom zadržavajući visoku vrijednost rMP -a. Potrebna su daljnja istraživanja odnosa između radne i validacijske populacije s većom efektivnom veličinom populacije jer smanjivanje veličine radne populacije, uz održavanje visoke vrijednosti rMP -a može omogućiti učinkovitiju alokaciju resursa u oplemenjivačkome programu kukuruza.
Bibliografija: 28 jed.
Summary ; Sažetak.
Keywords: Kukuruz -- Genomska selekcija -- Heritabilnost -- Genomska predviđanja -- Gustoća sjetve